WHATSAPP SEBAGAI MEDIA KOMUNIKASI: Studi Fenomenologi Motif Pengaturan Privasi Chatting Pengguna Whatsapp dalam Komunikasi Antarpribadi - dwi ridho aulianto (Prodi Ilmu Komunikasi Universitas Putera Batam, 2019)
The use of WhatsApp as media of communication is expected to facilitate people in doing remote interaction between person and community. Every people can set a privacy of chat on WhatsApp. However, people have several perceptions on it because it can be a symbol which has certain meaning. There are some people who are intentionally activate the privacy settings and some do not. Communication is established whether it remains effective or is hampered by chat privacy settings because someone cannot find out their online status, read messages or not. The purpose of this study is to determine the motives of privacy settings for whatsapp user chat in interpersonal communication. The study uses qualitative method with a phenomenological approach. The data collection is conducted through interviews with 13 whatsapp users who activated the chat privacy feature. It is taken from whatsapp researchers' friend contact. The results of the study on the motives of whatsapp chat privacy settings produce 2 main concepts, first is privacy (personal) which has 4 sub concepts (free, does not want others to be disappointed, so that others do not wait for an immediate answer, and important matters), and those second is work that has 2 sub concepts (business activities and office affairs).